D-Modules, Perverse Sheaves, and Representation Theory - Hotta, Ryoshi; Takeuchi, Kiyoshi; Tanisaki, Toshiyuki; SpringerLink (Online service) (Boston, MA : Birkhäuser Boston, 2008)
D-modules continues to be an active area of stimulating research in such mathematical areas as algebra, analysis, differential equations, and representation theory. Key to D-modules, Perverse Sheaves, and Representation Theory is the authors' essential algebraic-analytic approach to the theory, which connects D-modules to representation theory and other areas of mathematics. Significant concepts and topics that have emerged over the last few decades are presented, including a treatment of the theory of holonomic D-modules, perverse sheaves, the all-important Riemann-Hilbert correspondence, Hodge modules, and the solution to the Kazhdan-Lusztig conjecture using D-module theory. To further aid the reader, and to make the work as self-contained as possible, appendices are provided as background for the theory of derived categories and algebraic varieties. The book is intended to serve graduate students in a classroom setting and as self-study for researchers in algebraic geometry, and representation theory.
D-Modules and Perverse Sheaves -- Preliminary Notions -- Coherent D-Modules -- Holonomic D-Modules -- Analytic D-Modules and the de Rham Functor -- Theory of Meromorphic Connections -- Regular Holonomic D-Modules -- Riemann-Hilbert Correspondence -- Perverse Sheaves -- Representation Theory -- Algebraic Groups and Lie Algebras -- Conjugacy Classes of Semisimple Lie Algebras -- Representations of Lie Algebras and D-Modules -- Character Formula of HighestWeight Modules -- Hecke Algebras and Hodge Modules.
Keywords: MATHEMATICS; ALGEBRA; GEOMETRY, ALGEBRAIC; GROUP THEORY; TOPOLOGICAL GROUPS; MATHEMATICS; ALGEBRA; GROUP THEORY AND GENERALIZATIONS; TOPOLOGICAL GROUPS, LIE GROUPS; COMMUTATIVE RINGS AND ALGEBRAS; ALGEBRAIC GEOMETRY